PEMANFAATAN TEKNOLOGI AUGMENTED REALITY UNTUK MENGEKSPOS OBJEK BERSEJARAH PADA MUSEUM LAMPUNG - Zaini, T M (IIB Darmajaya, 2012)
Information found on museum_lampung in the form of object by the name of object, and also object function which in form of static text with small letter appearance and object object of museum static also, so that seen lose looks and is informative. Exploiting Of Technology of Augmented Reality used to develop a[n application which good for as supplementary information media at objects which there are in museum float in the form of text of virtual, object three ( 3) dimension, audio animation as well as video. Tools supporting this application is woke up among others use Artoolkitplus library software utilize to present information in the form of presented text by virtual, presented object threely ( 3) dimension and also in the form of animation. This application is also woke up by using Ianguage pemrograman of C++. used Marker assist to place model of virtual in real world by determining co-ordinate of marker relative to camera. This application is called by MULA-TAR abbreviation of Museum Lampung-Teknologi Augmented Reality. With this application presumably can make objects of museum which have been delegated entrust with marker can make the the object more seen interesting and informative, so that can improve society fascination and enthusiasm to Museum Float. â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦â¦ Keywords Â : Augmented Reality, ArtoolkitPlus, Marker, Museum Lampung